DESIGN OF AN AUTOMATIC SOLAR PANEL CLEANING SYSTEM BASED ON LDR RESISTANCE VALUES AND ELECTRICAL CURRENT FROM SUNLIGHT INTENSITY - Hanifah Agitha Baskara; Sandy Suryo Proyogo; Jamilah (TESLA: Jurnal Teknik Elektro, 2025)
The decline in solar panel performance due to dust and dirt is oneof the obstacles in the use of solar energy. This study discusses thedesign and implementation of an automatic cleaning system on solar panelsusing an LDR sensor to measure light intensity and a PZEM-017 sensorto read current values. The system works by monitoring the condition of the panel through comparison of current and light resistance values, then triggering wateringwhen dirt is detected on the panel surface. Testing the accuracy of the deviceshowed an average error of 1.10% in voltage, 0.048% in current, and0.09% in light resistance, indicating that the data readings were close to themeasurement values. The test was conducted under clear and partly cloudy conditions. Under clear weather conditions, the current recorded was less than 1.6A with LDR sensor resistance less than 110Ω, while under partly cloudy weather conditions, the current recorded was less than 1.5A with LDR sensor resistance less than 140Ω. At night or in rainy conditions, the current produced was 0.03–0.00A withLDR sensor resistance ≥ 510Ω, so that watering could not be carried out on thesurface of the solar panel. The test results prove that the system candistinguish between a decrease in panel performance due to dirt and low light intensity, so that watering is only carried out under appropriate conditions ABSTRAK Penurunan kinerja panel surya akibat debu dan kotoran menjadi salah satu kendala dalam pemanfaatan energi surya. Penelitian ini membahas perancangan dan implementasi sistem pembersih otomatis pada panel surya menggunakan sensor LDR untuk mengukur intensitas cahaya dan sensor PZEM-017 untuk membaca nilai arus. Sistem bekerja dengan memantau kondisi panel melalui perbandingan nilai arus dan resistansi cahaya, kemudian memicu penyiraman ketika terdeteksi adanya kotoran pada permukaan panel. Pengujian akurasi alat menunjukkan rata-rata error sebesar 1,10% pada tegangan, 0,048% pada arus, dan 0,09% pada resistansi cahaya, menandakan pembacaan data cukup mendekati nilai pengukuran. Pengujian dilakukan pada kondisi cerah dan cerah berawan, pada cuaca cerah, tercatat memiliki arus kurang dari 1,6A dengan resistansi sensor LDR kurang dari 110Ω, sedangkan pada cuaca cerah berawan terdapat arus kurang dari 1,5A dengan resistansi sensor LDR kurang dari 140Ω. Pada kondisi malam atau hujan arus yang dihasilkan sebesar 0,03–0,00A dengan resistansi sensor LDR ≥ 510Ω sehingga, tidak dapat melakukan penyiraman pada permukaan panel surya. Hasil pengujian membuktikan bahwa sistem dapat membedakan penurunan kinerja panel akibat kotoran dan rendahnya intensitas cahaya, sehingga penyiraman hanya dilakukan pada kondisi yang sesuai.